The family in late antiquity : the rise of Christianity and the endurance of tradition - Nathan, Geoffrey S. (Routledge, 2000)
"In the first comprehensive study of the family in the later Roman Empire - from approximately AD 300 to 550 - Geoffrey Nathan analyses the classical Roman family as well as early Christian notions of this most basic unit of social organization. Using these models as a contextual backdrop, Nathan then explores marriage, children, domestic servitude and other familial institutions in late antiquity. He brings together a diverse collection of sources, transcending traditional studies that have centred on the legal record."--Jacket.